Importing the basic map to the BIM model - Borkowski, Andrzej (Budownictwo i Architektura / Civil and Architectural Engineering, 2017)
BIM technology becomes more and more popular in the process of design of buildings and construction. Most models are created on maps for design purposes sent to designers by surveyors. However, the proposed changes, including the introduction of the Urban and Building Code, are intended to allow to design on the basic map. In some cases it will be possible to design buildings on the basic maps. The paper presents the possibility of importing a vector map made in CAD technology into the BIM model. Properly imported underlay is the basis for further design in BIM technology.